Research on 5G high-precision indoor positioning technology for smart parks - Baoyou WANG; Jingtao YANG; Saibin YAO; Haina YE; Zhihui WANG; Qiyuan ZHANG; Junfeng FU; Taishi JIN (Dianxin kexue)
The 5G cellular network not only provides wireless communication capabilities for terminals but also offers positioning functionalities.Firstly, the 3GPP 5G positioning technology was briefly outlined, followed by the proposal of the 5G indoor positioning technology road-map.The cloud-edge collaborative integrated positioning architecture, the 5G+X fusion positioning solution, as well as the 5G positioning solution for smart parks were included, with a detailed analysis of the architecture and process.These positioning solutions seamlessly addressed the issue of locating people or objects in areas where GNSS signals cannot reach, which could meet the positioning accuracy and timeliness requirements in different scenarios.The technology solution has been applied in the industry with meter-level positioning accuracy and second-level timeliness, which has been well evaluated by customers.